RILIGIUSITAS DAYAK AGABAG DALAM TRADISI DOLOB (Kajian Antropologis Berdasarkan Konsep Sistem Religi Emile Durkheim) - Agustinus Masterinus Laka Meko (Habitus : Jurnal Pendidikan, Sosiologi, dan Antropologi, 2021)
In culture there is what is called a religious system. The focus of this study is to look at the religious system of the Agabag Dayak tribe. In the Dayak community, the religious system is extracted from nature. Dayak Agabag discover their religious value through the Dolob Ritual, namely seeking truth and reconciliation in a problem that cannot be resolved amicably. With its anthropological review, this study looks at the position of Agabag Dayak culture in general before looking at the position of Dolob itself. Dolob culture is a symbol of human search for truth and reconciliation through water. The religious system in Dolob is seen from the perspective of Emile Durkheim in the theme of religion and belief which contains elements of prayer, tools, congregations, and others. This study also examines the Agabag Dayak culture by looking at Dayak culture in general and seeing its similarity. The critical note is that this culture is at the end of the road to being released. This is due to various advances in science and technology accompanied by a massive ecological crisis. The value of religiosity that is explored through nature, especially water, is challenged when they see that nature itself has been conquered by humans; magic power is lost.